2023
DOI: 10.1371/journal.pone.0284625
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and early-life exposure to traffic-related air pollution and allergic rhinitis in children: A systematic literature review

Abstract: Background Traffic-related air pollution (TRAP) is hypothesised to play a role in the development of allergic rhinitis (AR). Prenatal and early-life exposure to traffic-related air pollution is considered critical for later respiratory health. However, we could not find any articles systematically reviewing the risk of prenatal and early-life exposure to traffic-related air pollution for allergic rhinitis in children. Methods A systematic literature search of PubMed, Web of Science and Medline was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Exposure to moisture-related allergens, such as mold/damp stains and moldy/damp clothing or bedding, in the year preceding conception and during pregnancy, was notably linked to increased rhinitis prevalence. Living in close proximity to traffic roads intensified the adverse effects of household environmental factors while diminishing the protective effect of domestic dogs against childhood rhinitis ( 42 44 ). Additionally, family stress and male gender were identified as potential risk factors for allergic rhinitis in preschool children, particularly in the presence of early exposure to PM 10 and NO 2 ( 45 ).…”
Section: Prenatal and First-year Exposures And Ar Diagnosismentioning
confidence: 99%

Air pollution and rhinitis

Rosario,
Urrutia-Pereira,
Murrieta-Aguttes
et al. 2024
Front. Allergy
“…Exposure to moisture-related allergens, such as mold/damp stains and moldy/damp clothing or bedding, in the year preceding conception and during pregnancy, was notably linked to increased rhinitis prevalence. Living in close proximity to traffic roads intensified the adverse effects of household environmental factors while diminishing the protective effect of domestic dogs against childhood rhinitis ( 42 44 ). Additionally, family stress and male gender were identified as potential risk factors for allergic rhinitis in preschool children, particularly in the presence of early exposure to PM 10 and NO 2 ( 45 ).…”
Section: Prenatal and First-year Exposures And Ar Diagnosismentioning
confidence: 99%

Air pollution and rhinitis

Rosario,
Urrutia-Pereira,
Murrieta-Aguttes
et al. 2024
Front. Allergy
“…The researchers found that each increase of in prenatal exposure was associated with a 1.9-fold increased risk of the child being diagnosed with allergic rhinitis, as well as a 1.8-fold increase in parent-reported symptoms, which included nasal congestion, sneezing, and watery, itchy red eyes. 12 These hazard ratios reflect adjustment for potential confounding factors such as maternal smoking and age, family socioeconomic status, and residential greenness.…”
mentioning
confidence: 99%